Local Shear Conditions and Platelet Aggregates Regulate the Incorporation and Activity of Circulating Tissue Factor in ex-vivo Thrombi - Balasubramanian, Viji; Vele, Oana; Nemerson, Yale (Thrombosis and Haemostasis, 2002)
The presence of thrombogenic blood-borne or circulating tissue factor (cTF) has recently been demonstrated. These observations have implicated cTF to be a key determinant of thrombus propagation by depositing on platelets in nascent thrombi. Previously, we detected cTF by detergent solubilization and addition of phospholipids. We now report the direct demonstration of TF activity in ex-vivo thrombi. Collagen-coated substrates were exposed to native blood at shear rates of 0, 650, and 2000 s-1 for 10 min in a modified rotating Teflon cone and plate viscometer. Substrates were then gently rinsed to remove ‘loose’ (unadherent) components of blood. cTF activity was measured by adding a solution containing 10 nM FVIIa, 100 nM FX, and 5 mM CaCl2 to the substrates exposed to blood. Samples of this mixture were obtained at intervals for 30 min and the amount of Xa generated was quantified by adding a chromogenic substrate, Spectrozyme Xa, and measuring the increase in OD at 405 nm. Our studies show that a minimal amount of generated Xa (∼ 1nM) can be measured from ex-vivo thrombi. Static and shear samples generated the same amount of Xa, with the exception of blood subjected to 650 s-1 shear. At 650 s-1 shear rate, the amount of Xa generated reached a maximum of 4 nM at 5 min and then decreased to ∼1 nM. Immunohistological stains and fluorescent images demonstrate the presence of cTF antigen at 650 s-1 wall shear rate.
Keywords: Blood-borne tissue factor; platelets; thrombus; shear